Prognostic relevance of mitral regurgitation at different follow-up timepoints after transcatheter aortic valve implantation (TAVI): implications for therapeutic decision making?. (3rd October 2022) - Franz, M; Baez, L; Moebius-Winkler, S; Diab, M; Ibrahim, K; Kraeplin, T; Schulze, P C
Abstract: Background: Transcatheter aortic valve implantation (TAVI) has developed rapidly in the last decade and is now recommended as state-of-the-art treatment for elderly patients suffering from severe symptomatic degenerative aortic stenosis (AS). The extent of mitral regurgitation (MR) following TAVI is likely to be of prognostic relevance. This raises the question whether treating MR following TAVI improves outcome of patients with significant MR. Purpose: The current study was aimed to elucidate the prognostic value of MR at different follow-up (FU) timepoints after TAVI in a prospective real-world single-center registry study. Methods: A total of 445 patients with severe AS, which were treated by transfemoral TAVI, were included and a wide range of clinical, laboratory, functional and imaging parameters were prospectively assessed. Mortality was recorded at 30 days, 1 year and 2 years after TAVI. Complete FU data including echocardiography were available at 6 to 8 weeks (n=334) as well as 6 months (n=235) after TAVI. Results: All patients (mean age: 78.7±7.3 years, 52% female, mean STS score: 5±3.9%) were successfully treated by transfemoral TAVI using balloon- or self-expanding prostheses and showed mortality rates of 3.6% after 30 days, 16.4% after 1 year and 22.6% after 2 years. Moderate or severe (relevant) MR was detectable in 39% of the patients at baseline, in 27% of patients after 6 weeks (p=0.001) and in 28% of patients after 6 months (p=0.036, compared to baseline). Multivariate analysis identified independent predictors of 2-year mortality: clinical frailty scale and PAPsys at 6 to 8 weeks post-TAVI as well as BNP and relevant MR 6 months post TAVI. Among those parameters, MR after 6 months was the strongest predictor of long-term mortality (OR 3.192, CI 0.971–10.487, p=0.056). Kaplan-Meier survival analysis displayed significantly worse 2-year survival rates in patients suffering from relevant MR at 6 months (12.1% versus 4.8%, p=0.042). Conclusions: Taken together, this real-life single-center experience underlines the prognostic value of relevant MR 6 months after TAVI with respect to long-term survival. Interestingly, MR was not predictive at the 6 to 8 weeks FU suggesting that early remodeling includes MR with prognostic relevance in those patients. Whether MR treatment, e.g., by transcatheter edge-to-edge repair, will improve patient outcomes post-TAVI has to be tested in prospective trials. Funding Acknowledgement: Type of funding sources: None.